Verifying Existence and Composition of Workflow Activity Patterns in Real Process Models - Chiao, Carolina; Thom, Lucinéia Heloisa; Iochpe, Cirano; Reichert, Manfred (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2008)
In this paper we present a collection of high level workflow activity patterns based on the semantic of specific business functions (e.g., notification, task execution request, approval). In particular we discuss three pattern samples (approval, unidirectional and decision patterns). Moreover we gather the results of an analysis of their adoption on a wide set of real process models. The analyses showed that the patterns are not only enough but also necessary to model all the 190 process models which were subject of the investigation. We also show and discuss specific sequences or combination ofactivity patterns which were more often in the process models analyzed. In larger research we apply these patterns as well as the analyses results in the development of a suite for process modeling and normalization.